High-resolution vertical velocities and their power spectrum observed with the MAARSY radar – Part 1: frequency spectrum - Li, Qiang; Rapp, Markus; Stober, Gunter; Latteck, Ralph (Annales Geophysicae, 2018)
The Middle Atmosphere Alomar Radar System (MAARSY) installed at the island of Andøya has been run for continuous probing of atmospheric winds in the upper troposphere and lower stratosphere (UTLS) region. In the current study, we present high-resolution wind measurements during the period between 2010 and 2013 with MAARSY. The spectral analysis applying the Lomb–Scargle periodogram method has been carried out to determine the frequency spectra of vertical wind velocity. From a total of 522 days of observations, the statistics of the spectral slope have been derived and show a dependence on the Background wind conditions.